Coenzyme a biosynthesis and utilization in Plasmodium falciparum : drug targets for antimalarial chemotherapy - Macuamule, Cristiano Joao (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.